2015
DOI: 10.1007/s11207-015-0786-9
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Correlation of Sunquakes Based on Their Seismic and White-Light Emission

Abstract: Several mechanisms have been proposed to explain the transient seismic emission, i.e., "sunquakes," from some solar flares. Some theories associate high-energy electrons and/or white-light emission with sunquakes. High-energy charged particles and their subsequent heating of the photosphere and/or chromosphere could induce acoustic waves in the solar interior. We carried out a correlative study of solar flares with emission in hard-X rays (HXRs), enhanced continuum emission at 6173Å, and transient seismic emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The sunquake origin is normally indicated by a compact bright (source) kernel peaking during the flare verified by statistical tests (Matthews et al 2011). TD diagrams and acoustic holography have been shown to be complementary (Zharkov et al 2011b(Zharkov et al , 2013aBuitrago-Casas et al 2015).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The sunquake origin is normally indicated by a compact bright (source) kernel peaking during the flare verified by statistical tests (Matthews et al 2011). TD diagrams and acoustic holography have been shown to be complementary (Zharkov et al 2011b(Zharkov et al , 2013aBuitrago-Casas et al 2015).…”
Section: Introductionmentioning
confidence: 90%
“…Some authors have suggested radiative back-warming as a source of pressure transients that can produce acoustic waves (Donea et al 2006;Donea 2011). However, observations show that not all sunquakes are associated with WL emission, with some found in the locations with little or no HXR and whitelight emission (Matthews et al 2011;Buitrago-Casas et al 2015;Zharkov et al 2011a). Based on the complex magnetic picture of flaring events, another driving mechanism is proposed to be related to the Lorentz force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Kosovichev (2011) for a comprehensive review of the basic principles of global and local helioseismology and see Kosovichev (2006) for a review of the properties of sunquakes. For examples of sunquakes see, e.g., Martínez-Oliveros et al (2008) and examples by Judge et al (2014), Matthews et al (2015), and Buitrago-Casas et al (2015). Kosovichev (2014b) reports that the excitation impact strongly correlates with the impulsive flare phase and is caused by the energy/momentum transported from the energyrelease site(s) but that the physical mechanism is currently uncertain.…”
Section: Future Directions and Key Unanswered Questionsmentioning
confidence: 99%
“…The other authors explored radiative back-warming as the other source of pressure transients producing acoustic waves in flares (Donea et al 2006;Donea 2011). However, the observations showed that nearly half of sunquake locations are associated with little or absent white light emission (Matthews et al 2011;Buitrago-Casas et al 2015;Zharkov et al 2011a). And the third mechanism of sunquakes generation can occur in the locations of Lorentz force transients, which, supposedly, produce a well-directed magnetic impulse of Poynting vector towards the photosphere and subsequent magneto-acoustic waves (Hudson et al 2008;Fisher et al 2012).…”
Section: Introductionmentioning
confidence: 99%